Studi Evaluasi Kinerja Petani Karet - Saiful Bahri (LPPM ISNJ Bengkalis, 2016)
This study will analyze several mistakes of rubber farmer. These mistakes like burning in land cleansing, never care about tree slope and work me lonely. Burning in land cleansing known to destroy acts and rules. This action could make haze in the country and to more neighbour countries. To produce a rubber, a farmer must care about tree slope. It is so implicated on productivity especially for rubber’s exit. Finally, a farmer wished to recruits assistant for his partner to make the job become mild.